Atrial Fibrillation and Clinical Outcomes of Endovascular Thrombectomy for Acute Ischemic Stroke: A Meta‐Analysis of Adjusted Effect Estimates - Wei Zheng; Yi Tang; Huajing Lin; Huapin Huang; Hanhan Lei; Huiying Lin; Ying Huang; Xiaojuan Lin; Nan Liu; Houwei Du (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background The impact of atrial fibrillation (AF) on the clinical outcomes in patients with acute ischemic stroke (AIS) who received endovascular thrombectomy remains unclear. We aimed to perform a meta‐analysis of adjusted effect estimates to examine the association between the presence of AF and the clinical outcomes in patients with AIS who received endovascular thrombectomy. Methods and Results We searched PubMed, Embase, and the Cochrane database between January 1, 2013 and July 10, 2023. Data were meta‐analyzed to compare the outcomes among patients with AIS with and without AF who received endovascular thrombectomy. Our primary outcome was 90‐day functional independence defined as a modified Rankin Scale score of 0 to 2. Secondary outcomes included excellent independence (90‐day modified Rankin Scale score of 0–1), 90‐day mortality, symptomatic intracranial hemorrhage, and any intracranial hemorrhage. Eighteen observational studies comprising 16 096 patients with AIS (mean age, 70.1 years; women, 48.2%; 6862 with AF versus 9234 without AF) were included. There were no statistically significant differences for modified Rankin Scale score of 0 to 2 (pooled odds ratio [OR], 1.14 [95% CI, 0.95–1.37]; [95% prediction interval [PI], 0.72–1.80]), mortality (OR, 0.92 [95% CI, 0.79–1.08]; [95% PI, 0.77–1.11]), symptomatic intracranial hemorrhage (OR, 0.97 [95% CI, 0.71–1.32]; [95% PI, 0.43–2.17]), and any intracranial hemorrhage (OR, 1.08 [95% CI, 0.91–1.28]; [95% PI, 0.74–1.58]) among patients with AIS with and without AF. Conclusions This meta‐analysis detected no significant differences in 90‐day functional outcomes, mortality, and intracerebral hemorrhage risk after endovascular thrombectomy in patients with AIS with and without AF. Registration URL: https://www.crd.york.ac.uk/prospero; Unique identifier: CRD 42021293511.